Computational Literacy as an Important Element of a Digitized Science Teacher Education-A Systematic Review of Curriculum Patterns in Physics Teacher Education Degrees in Germany - Daniel Braun; Johannes Huwer (MDPI AG, 2023)
Computational literacy (CL) has become indispensable for teachers and learners as part of 21st-century skills. Therefore, corresponding models for teacher education are being further developed internationally from a scientific perspective. In parallel, content and competencies are being enhanced in the respective subjects at the curricular level of teacher training. In this context, we consider it important to examine the current status of this development. Since, to our knowledge, there are no comparable scientific studies, we have taken Germany as a representative example of the international education system and systematically analyzed the module handbooks of the physics teacher training courses at methodically selected universities. For this analysis, we used three research questions focusing on CL: In which physics content does CL play a role? Which computer science competencies or knowledge can be identified or derived? Are they described implicitly or explicitly? Our results suggest that CL is integrated very differently in terms of quantity and depth of content among the universities we examined. For example, there is often a very strong focus on computer-based data acquisition, but few programs also have specialized courses addressing CL more explicitly or integrate additional computer science competencies. CL is primarily taught in laboratory courses and frequently in subject-didactic courses. Nevertheless, the depictions presented in the purely subject-oriented and basic lectures lack specific computational literacy skills or knowledge. Furthermore, the fact that many programs only offer implicit descriptions of CL skills indicates that the integration of these skills has not progressed very far in practice.